IMPROVEMENT LEARNING OUTCOMES OF X MIPA-1 STUDENTS THROUGH THE STUDENT TEAMS ACHIEVEMENT DIVISION LEARNING METHOD IN THE AUTHORITY MATERIAL OF STATE INSTITUTIONS IN SMAN UNGGULAN 1 TANA TIDUNG 2018/2019 - Sepensi (Warta Pendidikan | e-Journal, 2021)
Education and learning are an interrelated unit. Learning is a form of the implementation of education. Gagne, Briggs, and Wager (1992) in Udin S. Winataputra (2007: 1.19) argue that learning is a series of activities designed to allow the learning process to occur in students. Students' PPKn learning achievement class X IPS 1 Integrated SMAN 1 Tana Tidung in understanding the concept of State Institution Authority is still low. This is due to several constraining factors that can come from the teacher and the students themselves. The obstacles from the teacher include the teacher using the monotonous method. Teachers do not understand learning methods that are in accordance with the learning material. As teachers, they should be creative in choosing methods, techniques, and learning models so that the teaching and learning process can take place actively, creatively, effectively and pleasantly. While the obstacles from students include: students 'learning motivation is still low and students' lack of creativity in learning. To improve student competence in understanding the concept of the Authority of State Teachers, it is necessary to try various methods, one of which is the "Student Teams Achievement Division" learning method. Thus it is hoped that the ability of students in understanding the concept of the Authority of State Institutions can be further improved. Therefore, this study aims to provide additional information and thoughts on how "Student Teams Achievement Division" is used in classroom learning. In addition, it is also to determine the increase in student achievement in the PPKn Subject so that in order to obtain higher quality learning outcomes, the learning method "Student Teams Achievement Division" is applied in discussing learning materials on the Authority of State Institutions in Indonesia.